Utilization of Jamun Fruit (Syzygium cumini L.) for Value Added Food Products - Samia El-Safy; Asmaa M. Khalifa; Aliaa A. Almashad; Azhar Mustafa Mohamed Khalil; Eman M. Hammad; Rokayya Sami; Amani H. Aljahani; Sunil Pareek; Mahmoud Helal; Sarah Alharthi; Ibrahim M. Taha (Journal of Food Quality, 2023)
The goal of this study is to draw attention to the vital nutrients, health advantages, and potential for encouraging the consumption of jamun fruits (Syzygium cumini L.) and making the most of their useful features to create valuable goods. In the current study, efforts have been made to evaluate the jamun fruit’s physicochemical characteristics and bioactive components. Moreover, ready-to-serve beverages, squash, syrup, and jam, have been prepared, and their quality has been monitored throughout the storage. Jamun fruit had an ovoid or spherical form and was a dark purple tint. The initial analysis of fruits showed 83.59% moisture, 17.56 °Brix, 3.63 pH, 328.50 mg cyd-3-Glu/100 g anthocyanin, 219.21 mg GAE/100 g total phenolics, 91.33 mg QE/100 g total flavonoids, and 91.33% antioxidant activity. High-performance liquid chromatography examination, revealed the existence of three main anthocyanin pigments, delphinidin 3, 5-diglucoside, petunidin 3, 5-diglucoside, and malvidin 3, 5-diglucoside, which were measured at 175.80, 156.50, and 83.12 mg/100 g, respectively. While the main phenolic compounds present were chlorogenic, gallic, caffeic, vanillic, and catechin, with respective concentrations of 14.22, 12.18, 10.33, 6.44, and 4.13 mg/100 g. Total soluble solids, pH, and total sugars increased with the storage of jamun products, but acidity, total phenolic, and anthocyanin contents declined. In conclusion, jamun is a fruit that has promise for the future of producing useful goods. The various jamun fruit-based products met good standards and were sensory-acceptable.